TELUSUR SEJARAH MOTIF BATIK PADA LOMAR BADUY - Tety Suparti; Khoirul Umam (BBPPMPV Seni dan Budaya Yogyakarta, 2023)
This research aims to investigate the history of batik motifs applied to the head band, or